The effect of acceptance and responsibility group therapy on the quality of sleep and quality of life of patients with anxiety disorders - Zhyvotovska, Анастасія; Isakov, Рустам (Psychosomatic Medicine and General Practice, 2024)
This text is the abstract of the report to the III Scientific and Practical Conference with International Participation "Psychiatry, Narcology, Clinical Psychology and General Medical Practice: Interdisciplinary Issues of the Present", March 22-23, 2024, Kyiv - online.